Die Begriffe 'Heiliger Geist' und 'Dreifaltigkeit Gottes' angesichts der afrikanischen religiösen Überlieferung - Bilolo, Mubabinge (Zeitschrift für Missionswissenschaft und Religionswissenschaft, 1984)
The author determines the African "avant-texte" (P Monsengwo) in relation to the concept of the Holy Ghost and the Trinity of God which represents pre- or extra-Christian theology, the fundamental concept of God and man in Africa, and forms the basis for the reception of the biblical message.... The concept of God as one being and also as Trinity or as community was known throughout Egypt, Nubia (Meroe), Ethiopia, and most regions of black Africa. The predilection of the African, from Alexandria to the present, for the concepts of Trinity and the Holy Ghost is explained by this pre- and extra-Christian theology. For the African, the Trinity does not only mean the truth of God's being, but the truth of man and of the world as well. Everybody has an obligation to develop his triadic structure–as monad, dyad, and community–and to develop his true self. For illustration the author proposes a Luba-terminology (Luba is one of the four national languages in Zaire) with regard to the Holy Ghost. This study in the field of history of religions offers a basis for developing an African pneumatology. [ed fr j].
Keywords: Africa – Religion; Christianity and African religions; Ethiopia – Religion; Gods and goddesses; African; Gods and goddesses; Egyptian; Holy Spirit – Comparative studies; Luba (African people); Theology – Africa; Trinity – Comparative studies